2020
DOI: 10.1111/his.14281
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow haemophagocytosis indicates severe infection with severe acute respiratory syndrome coronavirus 2

Abstract: Possible Relationship between SARS‐CoV‐2 infection, bone marrow haemophagocytosis and accelerated deterioration of COVID‐19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…There is not enough evidence of what proportion of patients with COVID-19 will show hemophagocytosis in reticuloendothelial systems. It was reported in an autopsy series in fatal cases of COVID-19 that 10 out of 15 patients showed evidence of erythrophagocytosis in bone marrow smears [ 16 ]. Another autopsy report in four COVID-19 patients with diffuse alveolar damage proved lymphophagocytosis in pulmonary lymph nodes in 3 patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is not enough evidence of what proportion of patients with COVID-19 will show hemophagocytosis in reticuloendothelial systems. It was reported in an autopsy series in fatal cases of COVID-19 that 10 out of 15 patients showed evidence of erythrophagocytosis in bone marrow smears [ 16 ]. Another autopsy report in four COVID-19 patients with diffuse alveolar damage proved lymphophagocytosis in pulmonary lymph nodes in 3 patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of macrophage activation-like syndrome, an extreme phenotype of bacterial sepsis, characterized by hyperferritinemia, coagulation disorders, liver dysfunction and high mortality, is also present in severe COVID-19. (8,132,133). Meanwhile, it has been demonstrated that the host response is characterized by a dysregulated activation of the innate immune system coupled with tissue damage by neutrophils and monocytes driving the interplay of inflammation and coagulation (129,130).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of unstable hemoglobin is another feasible hypothesis, as the SARS-CoV-2 may be entering the process of hemocytopoiesis, in addition to being highly mutagenic. Such mutagenicity results from the viral capacity to store genetic information also in RNA molecules, and this is the case with the SARS-CoV-2 ( 74 , 75 ). Thus, the SARS-CoV-2 would cause mutations and generate polymorphisms.…”
Section: Clinical Exam and Proteomics: Perspectivesmentioning
confidence: 99%